Avicultura de corte e consumo de água no semiárido paraibano - Pôrto, Júlio Cézar Gonçalves (2021)
Brazil is one of the largest producers and exporters of chicken meat in the world, a culture that is growing. In this sense, poultry farming has expanded to the semi-arid Northeast, where there are restrictions on drinking water and food. In the case of Paraíba, this has been evidenced in municipalities in the semiarid portion, such as Pocinhos, where poultry farming is the main agricultural activity in the municipality, located in the Immediate Geographic Region of Campina Grande. In view of this, it is prepared to establish the main characteristics of the activity, in particular, the consumption of water for the chicken in this geographic area, with these determinations being the main objectives. And as specific objectives: to diagnose the socioeconomic and environmental profiles of poultry farming; establish the main characteristics of the pluvial regime in the territorial cut of the municipality; and assess the potential for rainwater harvesting as an alternative to increase water supply and reduce the cost of broiler production. The methodological procedures consisted of two steps: the first, using published data related to the topic, with a search on the digital platforms of AESA, SUDENE, IBGE, USDA, among others. In the second, field data were collected, applying semi-structured questionnaires, containing 36 questions, on the socioeconomic and environmental aspects of the poultry farmer, chicken production and water demand, applied to fifty-three poultry farmers. The choice of aviaries was made according to the snowball method. The pluvial regime was established, by the criterion of climatological statistics, and estimated the potential volumes of rainwater catchment. The calculations, financial balance sheets and the elaboration of graphs and tables were made using an Excel spreadsheet. The main results show that poultry farming is a subsistence activity and requires technological investment and an alternative to increase water supply. The State of Paraíba ranks fifth in the Northeast and the quality of chicken meat requires cleaning of the aviary and phytosanitary control. The effective herd of chickens in the aforementioned municipality is, individually, larger than that of cattle, sheep, goats and pigs. The rainfall distribution model is irregular, asymmetry, the rainy season lasts from three to four months and has a chance of being dry. Even so, it has a high potential for capturing rainwater. The average water consumption per bird varies from 13.6 to 17.3 L depending on the application technology and the average fattening time is 45 days. There is a high potential for capturing rainwater, standing out as a viable alternative to local poultry farming, as it increases the supply of water and reduces production costs. Although it is an activity of great socioeconomic importance in the geographical area of Pocinhos, beef poultry farming currently needs public policies that enable investment in technological alternatives to increase the supply of drinking water.